A new species of Neoperla (Plecoptera: Perlidae) from Motuo County of Tibet, China and redescription of Neoperla perspicillata Zwick, 1980 - Li, Wenliang; Wang, Yingying; Li, Weihai (Zootaxa, 2021)
A new species of the stonefly genus Neoperla, N. bimaculata sp. nov. is described from Motuo County of Tibet of southwest China. The new species compared with related congeners. Based on strongly pigmented specimens, we redescribe the male adult of Neoperla perspicillata Zwick, 1980.